Body-mass index and obesity in urban and rural China: findings from consecutive nationally representative surveys during 2004–18 - Wang, Limin; Zhou, Bin; Zhao, Zhenping; Yang, Ling; Zhang, Mei; Jiang, Yong; Li, Yichong; Zhou, Maigeng; Wang, Linhong; Huang, Zhengjing; Zhang, Xiao; Zhao, Liyun; et al. (The Lancet (British edition), 2021)
In China, mean body-mass index (BMI) and obesity in adults have increased steadily since the early 1980s. However, to our knowledge, there has been no reliable assessment of recent trends, nationally, regionally, or in certain population subgroups. To address this evidence gap, we present detailed analyses of relevant data from six consecutive nationally representative health surveys done between 2004 and 2018. We aimed to examine the long-term and recent trends in mean BMI and prevalence of obesity among Chinese adults, with specific emphasis on changes before and after 2010 (when various national non-communicable disease prevention programmes were initiated), assess how these trends might vary by sex, age, urban–rural locality, and socioeconomic status, and estimate the number of people who were obese in 2018 compared with 2004. We used data from the China Chronic Disease and Risk Factors Surveillance programme, which was established in 2004 with the aim to provide periodic nationwide data on the prevalence of major chronic diseases and the associated behavioural and metabolic risk factors in the general population. Between 2004 and 2018 six nationally representative surveys were done. 776 571 individuals were invited and 746 020 (96·1%) participated, including 33 051 in 2004, 51 050 in 2007, 98 174 in 2010, 189 115 in 2013, 189 754 in 2015, and 184 876 in 2018. After exclusions, 645 223 participants aged 18–69 years remained for the present analyses. The mean BMI and prevalence of obesity (BMI ≥30 kg/m2) were calculated and time trends compared by sex, age, urban–rural locality, geographical region, and socioeconomic status. Standardised mean BMI levels rose from 22·7 kg/m2 (95% CI 22·5–22·9) in 2004 to 24·4 kg/m2 (24·3–24·6) in 2018 and obesity prevalence from 3·1% (2·5–3·7) to 8·1% (7·6–8·7). Between 2010 and 2018, mean BMI rose by 0·09 kg/m2 annually (0·06–0·11), which was half of that reported during 2004–10 (0·17 kg/m2, 95% CI 0·12–0·22). Similarly, the annual increase in obesity prevalence was somewhat smaller after 2010 than before 2010 (6·0% annual relative increase, 95% CI 4·4–7·6 vs 8·7% annual relative increase, 4·9–12·8; p=0·13). Since 2010, the rise in mean BMI and obesity prevalence has slowed down substantially in urban men and women, and moderately in rural men, but continued steadily in rural women. By 2018, mean BMI was higher in rural than urban women (24·3 kg/m2vs 23·9 kg/m2; p=0·0045), but remained lower in rural than urban men (24·5 kg/m2vs 25·1 kg/m2; p=0·0007). Across all six surveys, mean BMI was persistently lower in women with higher levels of education compared with women with lower levels of education, but the inverse was true among men. Overall, an estimated 85 million adults (95% CI 70 million–100 million; 48 million men [95% CI 39 million–57 million] and 37 million women [31 million–43 million]) aged 18–69 years in China were obese in 2018, which was three times as many as in 2004. In China, the rise in mean BMI among the adult population appears to have slowed down over the past decade. However, we found divergent trends by sex, geographical area, and socioeconomic status, highlighting the need for a more targeted approach to prevent further increases in obesity in the Chinese general population. China National Key Research and Development Program, China National Key Project of Public Health Program, and Youth Scientific Research Foundation of the National Center for Chronic and Noncommunicable Disease Control and Prevention, Chinese Center for Disease Control and Prevention.